ANALISIS KAPASITAS DAN KINERJA LALU LINTAS TERHADAP PEMBANGUNAN JALUR LRT FASE IB(Studi kasus: Ruas Jalan Pintu Air Manggarai - Mall Arion) - Nuryani; Muhrojin; R. Ichsan Moch Moch; Suparman (Jurnal Ilmu Teknik Terapan, 2025)
Road Tambak is the name of one of the roads in Central Jakarta, especially in the Manggarai area. road Tambak and Jalan Pemuda are two roads that connect each other. The pond road connects South Jakarta, Central Jakarta and East Jakarta by passing through Pramuka Road and crossing Jalan Matraman Raya and also Jalan Jendral Ahmad Yani. These two roads often experience traffic jams or delays during rush hours, which makes researchers want to conduct research on these two roads. The aim of this research is to find out what the traffic performance is like on Tambak Road and Pramuka Road and also to find out what factors cause delays on these two roads. Research data collection carried out from April 22 to May 3 2024 was in the form of data on vehicle speed, traffic volume, travel time and road capacity. From the results of this data collection, it was obtained that the longest travel time occurred on April 22 2024. And from the overall travel time data obtained by researchers, it can be concluded that the longest travel time with the most delays occurred on Friday, April 26 2024, precisely at 16.00-20.00 WIB. With a total time traveled of 1:07:55 seconds at vehicle speed the lowest was 16 km/hour, while the highest traffic volume occurred on May 3 2024 at 07.00 – 08.00 in the direction of Arion mall with a total of 3470 vehicles passing on the road section studied.